PENGGUNAKAN METODE NAÏVE BAYES PADA PROGRAM KEKHUSUSAN PRODI ILMU HUKUM UNIVERSITAS BUNG HATTA - Yanuarafi, Arisal (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
The Specific Program (PK) is the major for students of the Law Study Program at the Faculty of Law, Universitas Bung Hatta. Selection of the Specific Program is carried out after students have completed semester IV with several prerequisites that must be met. The application of the decision to select the Specific Program using the Naive Bayes method can simplify the administrative process of submitting PK from students and the resulting recommendation accuracy is above 82.1%. Training data is taken from the academic history of previous students who graduated on time.